2021
DOI: 10.3390/su13137412
|View full text |Cite
|
Sign up to set email alerts
|

Market Structure of Urban Waste Treatment and Disposal: Empirical Evidence from the Italian Industry

Abstract: In light of the organizational dynamics of services of economic interest, the regulation of municipal solid waste management is a critical issue to deal with so as to achieve sustainability goals in the coming decades. The European circular economy targets limit the share of municipal waste in landfills to a maximum of 10% by 2035. Consequently, waste-to-energy plants may temporarily become the primary option for residual unsorted waste. The municipal waste management chain comprises two consequential stages: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Overall, we found a low concentration in the upstream market for live cattle, with differing magnitudes of HHI for individual meat categories and over time. Except for Finland, which can be perceived as an outlier in the market concentration for most foodand beverage-producing sectors, Nes et al (2021) found similarly unconcentrated meat manufacturing markets in several other EU member states (Bulgaria, Czechia, Spain, France, Italy, Hungary, Portugal, Romania, Finland, and Sweden) [15]. A substantially higher market concentration was observed in the downstream market of slaughterhouses.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we found a low concentration in the upstream market for live cattle, with differing magnitudes of HHI for individual meat categories and over time. Except for Finland, which can be perceived as an outlier in the market concentration for most foodand beverage-producing sectors, Nes et al (2021) found similarly unconcentrated meat manufacturing markets in several other EU member states (Bulgaria, Czechia, Spain, France, Italy, Hungary, Portugal, Romania, Finland, and Sweden) [15]. A substantially higher market concentration was observed in the downstream market of slaughterhouses.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…In the literature, market concentration serves as a proxy for market participants' position in the supply chain. Peleckis (2022) and Di Foggia and Beccarello (2021) investigate non-food markets in this tradition [14,15]. Nes et al (2021) compared the concentration of EU food markets at several stages; however, the farm level was excluded [16].…”
Section: Introductionmentioning
confidence: 99%
“…Waste management is an indispensable area of activity that ensures the protection of human life and health and of the environment. In principle, without the existence of waste management, the development of modern civilization cannot be discussed in any aspect [42][43][44].…”
Section: Literature Review-providing Local Public Services and Municipally Owned Corporations 21 Local Collective Transport And Municipalmentioning
confidence: 99%
“…As shown on Figure 1, the waste management system is based on several steps and each one of them can be a potential source of odorants, i.e., collection, transport, treatment and disposal of wastes (mechanical-biological treatment facilities, composting plants, landfills, waste incinerators) [10][11][12][13]. The first step in the waste management chain is the collection of wastes by residents at households and residential areas and their transport by specialized vehicles to the adequate facilities for treatment and disposal.…”
Section: Introductionmentioning
confidence: 99%
“…The latter process is crucial for emission of odorous substances [2,7,9]. Moreover, chemical composition of those volatile mixtures can vary depending on the type of waste being processed, the stage of waste decomposition, the selected treatment method and its operating conditions, i.e., temperature, humidity or aeration [4,10,14]. The way that every step in waste management system is carried out can vary on national, regional and local scales [13].…”
Section: Introductionmentioning
confidence: 99%